Demand and Pattern for Endodontic Treatment in Jambi, Indonesia: Original Research Article - Azhar, Rodiyah; Prastuti Soewondo (HM Publisher, 2023)
There have been a growing number of patients demanding endodontic treatment to save their teeth. This study aimed to determine the pattern of demand and treatment need for root canal treatments at a tertiary healthcare facility in Jambi, Indonesia and update the dental literature with the demand and pattern of root canal treatments as seen in Jambi. This was a retrospective study. Data from 10.429 patients treated at conservative dentitistry clinic, at top two tertiary referral hospital in Jambi. Data was taken from January through December 2022 were reviewed. Data were analyzed using IBM SPSS Version 26. The association between categorical variables was assessed using the Chi-square test. Significance level was set at p<0.05. There were 5.940 patients age 15 to 70 years (Mean ± SD 34,60 ± 13,06) of which 3.564 (60.2%) were female and 2.376 (40%) male received root canal treatment. More female patients demanded for root canal treatment but treatment need was greater in female patients and increased with age. Demand for root canal treatment was more prevalent in those < 40 years of age. Central incisors were the most frequently root filled teeth in the maxilla and this was statistically significant (p=0.002). Prevalence of teeth diagnosed Pulpitis Irreversible were the most frequently endodontic treatment. The finding in this study corroborate those of several other previous studies.